Consumer Attitudes Toward an E–Mail Campaign to Durable Goods in Sri Lanka and Campaign Impact on Purchase Intention - Priyankara, Sampath; Pradhan, Ambira (Morgan Journal of Interdisciplinary Research Studies, 2024)
The majority of Sri Lankans are closely connected to the globalized environment and market, with significant improvements in environmental processes attributed to widespread internet usage. Over the past five years, Sri Lanka has experienced substantial growth in internet literacy. The advancements in Information Technology have facilitated a global network, enabling users to communicate without geographical or temporal constraints through email, which has become the predominant medium of communication and promotional campaigns. This research aimed to achieve the following objectives: measure the nature of attitudes towards durable goods, and assess the impact of attitudes towards an email campaign on purchase intention, utilizing the Consumer Tricomponent Attitude Model. The findings indicate a notable prevalence of email account usage for over a decade among respondents, particularly within the age group of 2-4 years, who habitually check their email accounts daily. More than 65% of respondents regularly view and read email newsletters, appreciating the convenience of hyperlinks that facilitate easy online purchases. The research concludes that, as a result of email newsletters, 22% of respondents express an intention to purchase durable goods online. This suggests that email newsletter campaigns for durable goods have the potential to influence consumer attitudes positively, leading to improved purchase intentions.